PENERAPAN KINESIO TAPING LEBIH EFEKTIF DARIPADA BANDAGE ELASTIC PADA INTERVENSI LATIHAN STABILISASI TERHADAP PENURUNAN NYERI AKIBAT CEDERA LIGAMEN KOLATERAL MEDIAL SENDI LUTUT - Syamsyul -; Luh Made Indah Sri Handari Adiputra; S Indra Lesmana (Sport and Fitness Journal, 2015)
Medial collateral ligament knee joint injury is one of movement disorders which causesimpaired mobility and function that inhibits daily activities. Pain and disability will beincreasing with the emergence of fatigue and atropism of muscles functioning as dynamicstabilizer. Pain commonly occurs on a condition of medial collateral ligament knee jointinjury type I, in acute and chronic phase. The purpose of this study to determine theeffectiveness of the application of Kinesiotaping and elastic Bandage on interventionstabilization exercises to decrease pain caused by injury to the medial collateral ligament ofthe knee joint.This study was experimental with randomized pre and post test group designwhich aimed to learn about causal phenomena by giving treatment to the study objects. Thestudy was carried out in Sport Health Clinic KONI Kota Langsa starting March to May 2015.The subjects of study were 20 patients who were classified into two groups, 10 subjects oftreatment group I given kinesiotaping application and 10 subjects of treatment group II givenelastic bandage application. The measuring tool of VAS (Visual Analogue Scale) was used tofind out any pain reduction. The results of study showed that group I and II indicating paindecrease with value of p = 0.008 (p<0.05) and p = 0.000 (p<0.005) respectively. Statisticalanalysis also showed a significant difference on both groups. Application of technique ongroup I was as effective as on group II to reduce pain due to medial collateral ligament kneejoint injury (p>0.05). From the above findings can be summarized that applications of bothkinesiotaping and elastic bandage on intervention of stabilization exercise are effective toreduce pain due to medial collateral ligament knee joint injury.